The Influence of Emotional Intelligence on the Performance of State Civil Servants in the West Sumbawa Regency Civil Service Police Unit - Syamsu, Badrus; Umar, Umar; Khadafie, Muammar (Jurnal Ilmiah Mandala Education (JIME), 2025)
The aim of this research is to determine the implementation and influence of emotional intelligence on the performance of State Civil Apparatus in the West Sumbawa Regency Civil Service Police Unit. The research method used is the research method Mix method. The population of this study was all ASNs in the West Sumbawa Regency Civil Service Police Unit, totaling 197 people. The sample for this research was 131 people taken using the Jalaludin Rahmat formula with a random proportional random sampling technique. The data collection technique for the ASN emotional intelligence variable used a questionnaire technique. The data analysis techniques used are correlation, regression and determination tests. Based on the results of the research data analysis, it can be concluded that: There is a close relationship between emotional intelligence and the performance of Civil Servants within the scope of the West Sumbawa Regency Civil Service Police Unit. Based on the regression equation it can be explained if ASN has good emotional intelligence, so ASN performance also increases.  Based on the calculation of the Coefficient of Determination (KD) to determine the magnitude of the contribution made by the emotional intelligence variable to the performance variable, it is 69.44%, meaning that the emotional intelligence variable contributes 69.44% to changes in the ASN performance variable. Meanwhile, the other 30.56% which also contributed to performance came from other factors, in this case not included in the study."